Reflections of older people about their experience of fall prevention exercise in the community- a qualitative study exploring evidence-based practice - Worum, Hilde (BMC Public Health, 2020)
BACKGROUND: Evidence-based practice (EBP) ensures that clinicians use effective interventions to achieve desired outcomes, thereby contributing to the best quality of care. The perspective of the participants is fundamental in EBP, as they have their own individual and meaningful rationale for participating in fall prevention. This study aims to explore community-dwelling older people reflections about their reflections about EBP in physiotherapy based on their experiences of a fall prevention exercise program. METHODS: We conducted semi-structured interviews with 16 community-dwelling older people (men = 7; women = 9). Data were analyzed using thematic analysis. RESULTS: The analysis revealed three themes: 1) the tension between knowing and doing, 2) the power of the therapist-participant relationship and the process of putting knowledge into action, and 3) research is interwoven with successful therapy and is an integral component of it. EBP was considered as a collective negotiation and learning process of creating knowledge for clinical practice. The negotiation between different types of knowledge must be performed in a transparent dialogue and through interactive collaboration between the persons involved. The participants appreciated that the research findings indicate that practice gives results. CONCLUSIONS: EBP was understood and utilized as a seal of approval and a “guarantee of high quality” treatment, and its effects varied based on older people’s preferences, needs, and skills. The therapist’s relational competence appeared to be crucial for the negotiation of various sources of knowledge relative to the older people’s preferences.